Exploring the Semantic Meaning and Structure of Slang in Instagram Captions - Fawzy, Hamida Rizka (Maliki Interdisciplinary Journal, 2025)
This article discusses the semantic aspects of slang terms used in Instagram captions. Language is dynamic and constantly evolving, especially in digital communication where informal expressions like slang are prevalent. Slang reflects social identity, group belonging, and modern communication styles. This study analyzes the lexical and contextual meanings of selected slang words, as well as their word formation processes such as acronyms, clipping, and imitative forms. The findings reveal that acronyms are the most dominant formation, indicating a preference for brevity and convenience in online interaction. Slang on Instagram serves not only as a tool of expression but also as a representation of digital culture. However, excessive or inappropriate use of slang may lead to miscommunication, especially across different generations or formal settings. This research contributes to understanding how language adapts to new platforms and offers insight into the semantic functions of online slang.